Model Implementasi Centralized Authentication Service pada Sistem Software As A Service - Muhammad Arfan (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2014)
The usage of cloud computing as continuously growing computing solutions becomes the base of organization and the company. On the other hand, the increase in the number of applications in the cloud system services raise another problems. Security issues become a threat in the authentication of the Cloud Computing services. Differences authentication model on every application that has been entered into cloud system become another threat for providers and users of cloud services. To solve these problems, a centralized authentication system is required in cloud applications using single sign-on protocol.